The effect of immunization with inactivated SARS-CoV-2 vaccine (CoronaVac) and/or SARS-CoV-2 infection on antibody levels, plasmablasts, long-lived-plasma-cells, and IFN-gamma release by natural killer cells - HAKLAR, GONCAGÜL; KARAHASAN, AYŞEGÜL; DURMUŞOĞLU, LÜTFİYE (My University, 2022)
Objectives: We evaluated the antibody response, natural killer cell response and B cell phenotypes in healthcare workers (HCW) who are vaccinated with two doses of CoronaVac with or without documented SARS-CoV-2 infection and unvaccinated HCWs with SARS-CoV-2 infection. Methods: HCWs were divided into four groups: vaccine only (VO), vaccine after SARS-CoV-2 infection (VAI), SARS-CoV-2 infection only (IO), and SARS-CoV-2 infection after vaccine (IAV). Anti-SARS-CoV-2 spike protein (Anti-S) antibodies were measured by Elecsys Anti–SARS–CoV–2 S ELISA kit. Memory B cells (CD19+ CD27+ ), plasmablast B cells (CD19+ CD138+ ) and long-lived plasma cells (LLPC; CD138+ CD19- ) were measured by flow cytometry in 74 patients. Interferon gamma (IFN-c) release by natural killer (NK) cells were measured by NKVue Test (NKMAX, Republic of Korea) in 76 patients. RT-PCR was performed with Bio-speedy COVID-19 qPCR detection kit, Version 2 (Bioexen LTD, Istanbul, Turkey). Results: The Anti-S antibodies were detectable in all HCWs (n: 224). The median Anti-S titers (BAU/mL) was significantly higher in VAI (620 25–75% 373–1341) compared to VO (136, 25–75% 85–283) and IO (111, 25–75% 54–413, p < 0.01). VAI group had significantly lower percentage of plasmablasts (2.9; 0– 8.7) compared to VO (6.8; 3.5–12.0) and IO (9.9; 4.7–47.5, p < 0.01) (n:74). Percentage of LLPCs in groups VO, VAI and IO was similar. There was no difference of IFN-c levels between the study groups (n: 76). Conclusion: The antibody response was similar between uninfected vaccinated HCWs and unvaccinated HCWs who had natural infection. HCWs who had two doses of CoronaVac either before or after the natural SARS-CoV-2 infection elicited significantly higher antibody responses compared to uninfected vaccinated HCWs. The lower percentages of plasmablasts in the VAI group may indicate their migration to lymph nodes and initiation of the germinal center reaction phase. IFN-c response did not differ among the groups.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Life Sciences; Health Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); IMMUNOLOGY; Life Sciences (LIFE); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Genel İmmünoloji ve Mikrobiyoloji; Research and Theory; Reviews and References (medical); Immunology; General Immunology and Microbiology; COVID-19; SARS-CoV-2 infection; Whole virion inactivated vaccine; CoronaVac; IFN-gamma; Anti-spike antibody; COVID-19; SARS-CoV-2 infection; Whole virion inactivated vaccine; CoronaVac; IFN-gamma; Anti-spike antibody